Development of Ethnoscience-Based Student Worksheets (LKPD) on Medicinal Plants to Improve Elementary School Students' Understanding - Fadiyah, Sarastya; Desstya, Anatri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Learning about medicinal plants so far has been textual and has not connected with daily life. The student worksheets (LKPD) used in learning have also not been contextual and have not linked to the ethnoscience aspects of certain regions. This study aims to: 1) Determine the urgency of developing ethnoscience-based LKPD on medicinal plant materials that are in accordance with the context of local plants; 2) test the validity of the LKPD; and 3) examine the practicality of ethnoscience-based LKPD in improving elementary school students' understanding of medicinal plant materials. This research uses a research and development (RnD) method by developing a 4D model (define, design, develop, disseminate), but is limited to the develop stage. The subjects of this study were teachers and fourth-grade students at Public Elementary School 1 Pandeyan, Ngemplak, Boyolali, and two lecturers as expert validators. Data collection techniques were carried out through observation, interviews, documentation, product validation sheets, and pretests. The analysis technique for qualitative data is conducted interactively, while quantitative data is analyzed descriptively. The research results show that: 1) The urgency of developing ethnoscience-based student worksheets reveals that the worksheets used so far have not included the introduction and understanding of medicinal plant concepts and have not linked ethnoscience in the Boyolali region. 2) The developed worksheets are declared highly feasible for use in learning after validation by material experts and media experts, with percentage results of 93.75% and 93.42%. 3) The developed worksheets are stated to be very practical for implementation in learning, with a result of 97.5%. The implications of this research indicate that the developed LKPD is ready to be applied in the field on a wide scale, with the need to establish hypotheses whose effectiveness needs to be tested.